Decommissioning and demolition 1990 proceedings, Second International Conference on Decommissioning Offshore, Onshore Demolition and Nuclear Works, held 24-26 April, 1990. venue, University of Manchester Institute of Science and Technology - Whyte, I. L. (Thomas Telford, 1990)
Presents new techniques for decommissioning and demolition of structures and confronts management issues. Developments in many fields including health and safety are addressed and communication between different sectors is encouraged.